Pemeriksaan Serologis IgG-IgM pada Pasien Demam Berdarah Dengue di RSUD Dr. Chasan Basoeri Ternate Periode Oktober - Desember 2021 - Nia Kurnia (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Dengue Fever (DF) is a viral infectious disease that is transmitted through the bite of the female Aedes aegypti and Aedes albopictus mosquitoes. This virus is a single-stranded RNA virus in the genus Flavivirus of the family Flaviviridae which has 4 serotypes (DEN-1, DEN-2, DEN-3, DEN-4). Indonesia is one of the dengue endemic countries. North Maluku is currently one of the provinces that are endemic for dengue fever. DF cases appear almost every year in North Maluku, especially in the city of Ternate. This study is a descriptive cross-sectional study to determine the distribution of samples based on gender, age, and serological examination of IgM-IgG antidengue antibodies in patients infected with dengue virus in RSUD DR. Chasan Basoeri Ternate period October to December 2021. The study was conducted on 12 patients. The results of this study showed that the most gender on serological examination, namely male sex more than female sex, namely as many as 7 patients (58.3%). The highest age range was 6-10 years as many as 7 patients (58.3%). The results of the IgM (+) IgG (-) examination were 3 patients (25%) in the age range of 6 to 10 years. The results of the IgM(-) IgG (+) examination were also 3 patients (25%) and IgM (+) IgG (+) as many as 1 patient (18.3%) in the age range of 6 to 10 years. Keywords: Dengue Fever, serology, IgG, IgM.